Competency Framework Development for Human Resource Management in Small-Sized Industries - Adkine, Neelam Mayur (Digital Repository of Theses, 2025)
This study scrutinizes the impact of a Competency Framework Development for Human Resource efficacy in Small-Sized Industries, AI integration enables improved decision making. Addressing the first query, the research evaluates how such a framework aids in gauging personnel suitability and adaptability, thereby leveraging AI for enhanced performance. To the second query, the study delves into how competency framework streamline personnel allocation by trimming time and cost by strategically adaptation of individuals into the roles, leading to improved job satisfaction, productivity, and business efficiency. The research employs a mixed-methods approach, intertwining quantitative and qualitative methods. The methodology incorporates structured surveys and semistructured interviews, revealing comprehensive insights. Acknowledging possible dissenting viewpoints, the study analyzes both agreement and disagreement to provide a well-rounded perspective. Furthermore, the research extends to examining competency variances between Industries with and without HR departments, promising avenues for future exploration. In summation, this study will find answer for research questions and test hypothesis to conclude results to contribute a holistic Development of Competency Framework Model, transformative potential in Small-Sized Industries, elucidating its influence on having HR, personnel evaluation, cost reduction, and uses of AI in business optimization.